The elasticity of substitution between imported and domestically produced goods in Germany - Ulrich Lächler (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1984)
The elasticity of substitution concept has become one of the mainstays in the measurement of price responsiveness not only in production theory, where it originates, but also in the study of international trade. It has been applied, for example, in the context of the world demand for exports from two competing sources (Richardson (1973), Zelder (1958)),to estimate one country's relative demand for imports from competing foreign sources (Hickman and Lau (1973), Morgan and Corlett (1951)), and to estimate one country's demand for imports relative to domestic substitutes (Alaouze (1\9 77), Mutti (1977)). The present paper pursues the last issue by examining the elasticity of substitution between the demand for commodity imports and domestic substitutes in the Federal Republic of Germany, using data disaggregated at an industry level.
Keywords: 330